2017
DOI: 10.1556/004.2017.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the nucleic acid binding features of the PRRSV 7ap and its ability to induce antinuclear antibodies

Abstract: A short alternative open reading frame named ORF7a has recently been discovered within the nucleocapsid gene of the porcine reproductive and respiratory syndrome virus (PRRSV) genome. Proteins (7ap) translated from the ORF7a of two divergent strains -a type I and a type II -are able to completely reduce the motility of nucleic acids at relatively high molar charge ratios in gel retardation assays indicating strong dsDNA-and ssRNA-binding capability. Conserved RNAand DNA-binding properties suggest that nucleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Of note, the emerging evidence indicated that a novel alternative open reading frame was discovered in XM-2020, with lower transcriptional levels, encoding a 37-amino acid peptide inside the coding region of the N gene, named ORF7a (Table S3). This finding was supported by another study, and further experimental strategies are needed to validate the functional relevance of this potential short peptide during PRRSV infection [32,33]. Although the authentic expression profiles of these N-terminal truncated ORFs and their potential functions remain unclear, they represent an additional level of transcriptome complexity and greatly expand our earlier knowledge of the coding capacity for PRRSV.…”
Section: Gene Predictions and Annotationsmentioning
confidence: 58%
“…Of note, the emerging evidence indicated that a novel alternative open reading frame was discovered in XM-2020, with lower transcriptional levels, encoding a 37-amino acid peptide inside the coding region of the N gene, named ORF7a (Table S3). This finding was supported by another study, and further experimental strategies are needed to validate the functional relevance of this potential short peptide during PRRSV infection [32,33]. Although the authentic expression profiles of these N-terminal truncated ORFs and their potential functions remain unclear, they represent an additional level of transcriptome complexity and greatly expand our earlier knowledge of the coding capacity for PRRSV.…”
Section: Gene Predictions and Annotationsmentioning
confidence: 58%
“…The localisation of the protein in multiple cellular compartments and the presence of predicted DNA binding and activator domains indicate pleiotropic functions of 3a that most probably involve the reprogramming of the transcriptional regulation of the infected cells. Viral proteins with similar multiple (cytosolic and nuclear) localisations were identified in several different viruses (e. g. 7ap of PRRSV, X protein of hepatitis B virus, μ2 of reovirus T1L (Mbisa et al, 2000;Henkler et al, 2001;Ma et al, 2011;Olasz et al, 2016Olasz et al, , 2017aRivera-Serrano et al, 2017) with proven nucleic acid binding and/or transcription regulating capabilities. Acta Veterinaria Hungarica 66, 2018 Protein 3b was found to localise in the mitochondrion and the nucleolus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ORFs 2a to 4 code for the membrane-associated glycoproteins GP2, GP3, and GP4 and a nonglycosylated membrane polypeptide, protein E. ORFs 5 to 7 encode three major structural proteins. These are, respectively, the envelope glycoprotein GP5, the nonglycosylated membrane protein M, and the nucleocapsid protein N, while two alternative ORFs overlapping with ORF5 and ORF7 code for the ORF5a protein and the 7ap protein, respectively [25].…”
mentioning
confidence: 99%